Neodymium-140 DOTA-LM3: Evaluation of an In Vivo Generator for PET with a Non-Internalizing Vector - Severin, Gregory W.; Kristensen, Lotte K.; Nielsen, Carsten H.; Fonslet, Jesper; Jensen, Andreas I.; Frellsen, Anders F.; Jensen, K. M.; Elema, Dennis R.; Maecke, Helmut; Kjær, Andreas; Johnston, Karl; Köster, Ulli (Frontiers in Medicine, 2017)
140Nd (t1/2=3.4 d), owing to its short-lived positron emitting daughter 140Pr (t1/2 = 3.4 min), has promise as an in vivo generator for positron emission tomography (PET). However, the electron capture decay of 140Nd is chemically disruptive to macrocycle-based radiolabeling, meaning that an in vivo redistribution of the daughter 140Pr is expected before positron emission. The purpose of this study was to determine how the delayed positron from the de-labeled 140Pr affects preclinical imaging with 140Nd. To explore the effect 140Nd was produced at CERN-ISOLDE, reacted with the somatostatin analog, DOTA-LM3 (1,4,7,10 tetraazacyclododecane 1,4,7 tri acetic acid 10 acetamide N - p-Cl-Phecyclo(D-Cys-Tyr-D-4-amino-Phe(carbamoyl)-Lys-Thr-Cys)D-Tyr-NH2) and injected into H727 xenograft bearing mice. Comparative pre- and post-mortem PET imaging at 16 hours post-injection was used to quantify the in vivo redistribution of 140Pr following 140Nd decay. The somatostatin-receptor-positive pancreas exhibited the highest tissue accumulation of 140Nd-DOTA-LM3 (13% ID/g at 16 h) coupled with the largest observed redistribution rate, where 56 ± 7% (n = 4, mean ± s.d.) of the in situ produced 140Pr washed out of the pancreas before decay. Contrastingly, the liver, spleen and lungs acted as a strong sink organs for free 140Pr3+. Based upon these results we conclude that 140Nd imaging with a non-internalizing vector convolutes the biodistribution of the tracer with the accumulation pattern of free 140Pr. This redistribution phenomenon may show promise as a probe of the cellular interaction with the vector, such as in determining tissue dependent internalization behavior.